Crisdesalazine alleviates inflammation in an experimental autoimmune encephalomyelitis multiple sclerosis mouse model by regulating the immune system - Su-Min Park; Yong-Hun Oh; Ga-Hyun Lim; Ju-Hyun An; Jin-Hwan Lee; Byoung-Joo Gwag; So-Jung Won; Kyoung-Won Seo; Hwa-Young Youn (BMC Neuroscience)
Abstract Microglia/macrophages participate in the development of and recovery from experimental autoimmune encephalomyelitis (EAE), and the macrophage M1 (pro-inflammatory)/M2 (anti-inflammatory) phase transition is involved in EAE disease progression. We evaluated the efficacy of crisdesalazine (a novel microsomal prostaglandin E2 synthase-1 inhibitor) in an EAE model, including its immune-regulating potency in lipopolysaccharide-stimulated macrophages, and its neuroprotective effects in a macrophage-neuronal co-culture system. Crisdesalazine significantly alleviated clinical symptoms, inhibited inflammatory cell infiltration and demyelination in the spinal cord, and altered the phase of microglial/macrophage and regulatory T cells. Crisdesalazine promoted the M1 to M2 phase transition in macrophages (immunomodulation) and reduced neuronal necrosis (neuroprotection) in vitro. This is the first study to directly demonstrate the therapeutic effects of a microsomal prostaglandin E2 synthase-1 inhibitor in an EAE model and its ability to alter macrophage polarization, suggesting that it may be a new therapeutic option for the treatment of patients affected by multiple sclerosis and other autoimmune diseases.